PEMETAAN KARBON ORGANIK TANAH LAHAN SAWAH DI KECAMATAN PALLANGGA KABUPATEN GOWA - Saida, Saida; Robbo, Anwar; A, Rani Iswanti (Percetakan Umi Toaha Makassar, 2025)
Carbon is an important nutrient for building soil organic matter which is needed in agricultural activities. Cultivation activities in paddy fields increase carbon gas emissions into CO2 into the atmosphere, especially in irrigated rice fields. This study aims to determine the level of content and map the distribution of organic carbon in paddy fields in Pallangga District, Gowa Regency. The research was carried out in Pallangga District, Gowa Regency from December 2021–January 2022. The research method used the free grid method with a total of 33 samples and map interpolation using ArcGIS software. The results showed that the status of the level of organic carbon content was in the very low to low criteria. The level of organic carbon content is very low, namely T8 8.83 tons/ha, T9 7.85 tons/ha, T10 9.74 tons/ha, and T11 9.20 tons/ha. While the low organic carbon content is T1 which is 12.76 tons/ha, T2 points 11.76 tons/ha, T3 10.92 tons/ha, T4 12.98 tons/ha, T5 12.90 tons/ha, T6 11 .66 tons/ha, and T7 is 13.06 tons/ha. The mapping area of low criteria organic carbon distribution is only 27% or 850 ha of the total area, while 73% or 2,338 ha is categorized as very low. Based on these results, it is necessary to take action on agricultural land management, especially rice fields that are friendly to carbon emissions, one of them is stabilizing the use of chemical and organic fertilizers, the organic material produced by such cultivation activities as straw is not burned and returned to the soil so that it could maintain fertility and quality of soil and improve the physical, chemical, and biological conditions needed for sustainable agricultural development.